Nonagermanide Zintl Clusters with Mg2+ Counter Ions. Issue 19 (11th April 2022) - Wallach, Christoph; Klein, Wilhelm; Fässler, Thomas F.
Abstract: Ion exchange processes are rarely investigated with respect to tetrel element Zintl clusters. We now discovered that the addition of Mg complexes to nonagermanide anions comprising K + counter cations results in an exchange of the alkali ions by alkaline earth cations. Upon stirring K[Ge9 {Si(TMS)3 }3 ] (TMS=trimethylsilyl) and Mg(NacNac Mes )I (NacNac Mes = N, N' ‐bis(2, 4, 6‐trimethylphenyl)‐ β ‐diketiminate) in MeCN the product [Mg(NacNac Mes )(MeCN)4 ][Ge9 {Si(TMS)3 }3 ]⋅ MeCN is formed. Reactions of Mg(NacNac Mes )I with K4 Ge9 in liquid ammonia as a solvent yielded [K[2.2.2]crypt]4 [Mg(NacNac Mes )(NH3 )4 ]2 [Ge9 −Ge9 ] ⋅ 32.58 NH3 featuring a mixed alkali/alkaline earth metal cationic sphere and an oxidative coupling of the [Ge9 ] 4− clusters. From comparable reactions of [Mg(NacNac Mes )]2 with K4 Ge9 or K12 Ge17 in liquid ammonia crystals of [K[2.2.2]crypt][NacNac Mes ] ⋅ NH3 and [K(18‐crown‐6)][NacNac Mes ] ⋅ 3 NH3, respectively, were isolated. All compounds were characterized by means of single crystal structure determination. Abstract :